2016
DOI: 10.1016/j.adolescence.2016.07.005
|View full text |Cite
|
Sign up to set email alerts
|

The Prosocial Cyberball Game: Compensating for social exclusion and its associations with empathic concern and bullying in adolescents

Abstract: In this study we examined prosocial compensating behavior towards socially excluded ingroup and outgroup members by using a 'Prosocial Cyberball Game' in 9-17 year old Dutch adolescents (N = 133). Results showed that adolescents compensated for the social exclusion of an unknown peer in a virtual ball tossing game, by tossing the ball more often to that player in compensation conditions compared to the fair play condition. The proportion of tosses towards the excluded player did not significantly differ as a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(40 citation statements)
references
References 51 publications
(79 reference statements)
1
38
0
1
Order By: Relevance
“…We calculated this ratio by dividing the number of tosses to Player 2 by the total number of tosses to all players (van der Meulen et al, 2016;Vrijhof et al, 2016). Paired t-tests were performed to study prosocial compensating behavior.…”
Section: Behavioral Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We calculated this ratio by dividing the number of tosses to Player 2 by the total number of tosses to all players (van der Meulen et al, 2016;Vrijhof et al, 2016). Paired t-tests were performed to study prosocial compensating behavior.…”
Section: Behavioral Resultsmentioning
confidence: 99%
“…To measure reactions to observed social exclusion we used an experimental fMRI adapted version of the Prosocial Cyberball Game (PCG) (Riem et al, 2013;van der Meulen et al, 2016;Vrijhof et al, 2016). In this game, participants see four classical Cyberball figures on the screen (Williams et al, 2000).…”
Section: Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…In other words, children take account of both social and moral concerns in their judgments of intragroup exclusion scenarios. Elsewhere it has been shown that, given the opportunity, children will compensate those who their group earlier excluded from a cyberball game (Vrijhof et al 2016;Will et al 2013). There is then good evidence of children's acute sensitivity to ingroup members' behavior that takes account of social and cognitive variables, evidence that children respond emotionally at the interpersonal and intergroup level and evidence that intergroup exclusion has deleterious outcomes.…”
Section: Group-based Emotionmentioning
confidence: 99%